Effect of mixed tropical hardwood kraft pulp and polyacrylamide types on magnetite retention in lumen loaded handsheets - Ainun Zuriyati Mohamed,; Sarani Zakaria,; Roslinda Shamsuddin,; Mustaffa Abdullah, (Universiti Kebangsaan Malaysia, 2010)
This paper reports on the preparation of magnetic lumen loaded handsheets from bleached and unbleached mixed tropical hardwood kraft pulps. The lumen coating technique is a physical approach whereby fillers were deposited inside the fibre lumen. In order to produce magnetically responsive fibres, magnetic fillers were loaded into the fibre lumen. The magnetic filler chosen was magnetite which is usually used to make mylar as found in a diskette. Low and high molecular weights of polyacrylamide (PAM) were used as retention aids. The effect of different molecular weight of PAM on filler content in the bleached and unbleached handsheets were studied. The results showed that the amount of fillers deposited in the pulp fibres increased with increasing molecular weight of PAM using both pulps. However the bleached pulps gave better lumen loading than the unbleached when using high molecular weight of PAM.